SISTEM INFORMASI PERPUSTAKAAN UNIVERSITAS SAHID SURAKARTA BERBASIS OBJEK - Joko Cahyono; Dahlan susilo; Sri Huning Anwariningsih (Universitas Sahid Surakarta, 2012)
The Library of Sahid University at Surakarta still used a manual data processing system by a human. This procedures has some weakness, specially mistake error andused a long time during searching or recording the data.The purpose of this research is to develop the information and data processing system at Sahid University Library. Thesystem that been developed is information and data processing that previously done by human converted to computer based system. These changes are necessary to facilitate data processing and presentation of information properly in order to avoid the weakness a manual system. This research use an object methode, that built depend on library necessary both visitors and library staff. A system can be called qualified if it meets several criteria ofquality. Software quality measurement in this study using McCall methodes with five factors include of correctness, reliability, eficiency, usability and maintenance. Thismethode had chosen because of this methode is familiar and good to measure the quality of software. The resulting product of this research is library information system based from the object that built depend on library necessary. The advantages of this system is moreeasy to finding a book or catalog like borrowing or repayment transactions, input of book data and member and also more easy to make the reports. Finally, the result is thesystem with McCall methodes have 77,151% total quality, that means this system can be applied at Sahid University Library to simplify the data processing and presentation all about Library information.